A simulated risk assessment of human-robot interaction in the domestic environment - Kaonain, Tamanna E; Abdul Rahman, Mohd Azizi; Mohammed Ariff, Mohd Hatta; Mondal, Kuheli (IAES International Journal of Robotics and Automation (IJRA), 2020)
In human-robot interaction, the use of collaborative robots or cobots in many industries is of major importance to researchers in human-robot interaction (HRI). The interaction between human robot carries several challenges, the greatest being the risk of human injury. In addition to reducing the proximity between robots and humans, increased difficulty of human-robot encounters raises the likelihood of accidents only. This paper proposes a virtual collaborative robot in the simulated non-industrial workspace. The safety during human-robot interaction using simulation software was investigated by measuring the risks for planning and control. A reactive robot controller was formulated to minimize the risk during human-robot interaction. A Gazebo software is used in this article, written in Python language, to replicate complex environments that a robot can face. This paper also investigated the robot’s speed. It can be reduced before a collision with a human about to happen, and it minimized the risk of the collision or reduced the damage of the risk. After the successful simulation, this can be applied to the real robot in a practical domestic environment.